1.2 Ga thermal metamorphism in the Albany-Fraser Orogen of Western Australia: consequence of collision or regional heating by dyke swarms? - Dawson, G.; Krapez, Bryan; Fletcher, Ian; McNaughton, Neal; Rasmussen, Birger (Geological Society Publishing House, 2003)
Compressive fabrics in the Late Palaeoproterozoic Mount Barren Group of the Albany-Fraser Orogen, southwestern Australia, record Mesoproterozoic collision between proto-Australia and proto-Antarctica. Petrographical evidence establishes that peak thermal metamorphism produced largely random growth of kyanite, staurolite, biotite, monazite and xenotime that overprinted those fabrics. SHRIMP U-Pb geochronology of xenotime and monazite yields an average age of 1205 10 Ma. Thermal metamorphism therefore occurred at least 45 Ma after fabric formation, and was unlikely to have been caused by collision. Rather, thermal metamorphism overlapped with the emplacement of 1215-1202 Ma dyke swarms into the Orogen and the adjacent Yilgarn Craton, and was followed by emplacement of 1200-1180 Ma granites. Regional heating associated with mafic magmatism was the probable cause of thermal metamorphism, but previous proposals that the dyke swarms were the consequence of collision or extensional orogenic collapse cannot be substantiated. A regional thermal anomaly, craton-scale extension and adiabatic decompression melting of the asthenosphere are implied, but causal mechanisms such as a mantle plume or intracontinental rifting require substantiation from other parts of East Gondwana. The significant time gap between orogenic deformation and thermal metamorphism implies that metamorphism in many other orogens may not necessarily be due to compressive tectonics.